2015
DOI: 10.1039/c5ta04863j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of thin film AuPd alloys and their investigation for electrocatalytic CO2reduction

Abstract: Alloying of Au and Pd leads to new synergistic catalytic effects, providing insights into electrocatalytic CO2 reduction on alloy surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
112
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(122 citation statements)
references
References 28 publications
(35 reference statements)
7
112
0
2
Order By: Relevance
“…Hahn et al. employed electron‐beam deposition techniques to prepare Au‐Pd alloy thin films with varying atomic compositions and demonstrated that the alloys showed improved selectivities for HCOO − compared to either Au or Pd . Another level of control over the selectivity of CO 2 reduction could be achieved by growing thin Pd layers at Au surfaces.…”
Section: Introductionsupporting
confidence: 76%
“…Hahn et al. employed electron‐beam deposition techniques to prepare Au‐Pd alloy thin films with varying atomic compositions and demonstrated that the alloys showed improved selectivities for HCOO − compared to either Au or Pd . Another level of control over the selectivity of CO 2 reduction could be achieved by growing thin Pd layers at Au surfaces.…”
Section: Introductionsupporting
confidence: 76%
“…10 However, their implementation at an industrial scale is unsustainable and has limitations owing to the scarcity of noble metals. [7][8][9][10] Previous studies by Hori and coworkers have demonstrated that Cu is unique compared with other metals in its ability to produce hydrocarbons at potentials more negative than −1 V vs RHE. 11 Nevertheless, the large overpotential renders the process inefficient.…”
mentioning
confidence: 99%
“…Indeed, the effects of alloying are shown to take advantage of the electronic and geometric effects of the individual metals to create synergistic effects. For instance, Au and Pd are known to be selective for the generation of only CO during CO 2 RR but Au–Pd alloy is capable of generating formate with 10% FE . Similarly, a Pt–Pd alloy was reported to demonstrate a very high FE HCOO − of 88% at −0.4 V …”
Section: Active Sites In Metal‐based Catalystsmentioning
confidence: 99%